PNEUMOCOCCAL INFECTION — IN THE CENTRE OF ATTENTION AGAIN - S.V. Sidorenko (Вопросы современной педиатрии, 2009)
This article present a general review on pneumococcal infection, its prevalence, clinic types in children in Russia and worldwide. Description of S. pneumoniae serotypes' distribution and its influence at clinical manifestation of pneumococcal infection and vaccination effectiveness is provided. Author evaluates perspectives of pneumococcal infection prevention by vaccination with pneumococcal conjugated 7-valent vaccine in Russia.Key words: children, pneumococcal infection, vaccination, pneumococcal conjugated 7 valent vaccine.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(3):82-87)